2017
DOI: 10.1186/s12933-017-0545-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-binding protein is associated with arterial stiffness in patients with type 2 diabetes: a cross-sectional study

Abstract: BackgroundLipopolysaccharide (LPS)-binding protein (LBP) is an acute-phase reactant that mediates immune responses triggered by LPS. Recent evidence indicates the association of circulating LBP levels with obesity, diabetes, and cardiovascular diseases. In this study, we aimed to investigate the relationship between serum LBP levels and arterial stiffness in patients with type 2 diabetes.MethodsA total of 196 patients with type 2 diabetes, including 101 men and 95 women, were enrolled in this cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 53 publications
6
23
0
Order By: Relevance
“…Furthermore, circulating plasma LBP levels were significantly and positively associated with BMI, systolic blood pressure, aspartate aminotransferase, alanine aminotransferase, total cholesterol, LDL-C, fasting glucose and insulin, and insulin resistance in the study of Moreno-Navarrete et al [9]. Serum LBP levels were also positively correlated with the parameters of obesity, insulin resistance, and inflammation in diabetic subjects as mentioned in a previous Japanese study [23]. In a prospective observational study involving 49 obese subjects undergoing bariatric surgery and 17 controls, plasma LPS was positively correlated with cardiometabolic risk factors, including triglycerides, systolic blood pressure, and BMI and was negatively correlated with HDL cholesterol [24].…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, circulating plasma LBP levels were significantly and positively associated with BMI, systolic blood pressure, aspartate aminotransferase, alanine aminotransferase, total cholesterol, LDL-C, fasting glucose and insulin, and insulin resistance in the study of Moreno-Navarrete et al [9]. Serum LBP levels were also positively correlated with the parameters of obesity, insulin resistance, and inflammation in diabetic subjects as mentioned in a previous Japanese study [23]. In a prospective observational study involving 49 obese subjects undergoing bariatric surgery and 17 controls, plasma LPS was positively correlated with cardiometabolic risk factors, including triglycerides, systolic blood pressure, and BMI and was negatively correlated with HDL cholesterol [24].…”
Section: Discussionsupporting
confidence: 55%
“…On the contrary, it might be argued that the presence of elevated levels of LBP protein remains an indirect clue to the role of endotoxin. Nevertheless previous studies [28][29] suggested that LBP is a useful parameter for assessing the biological activity of circulating endotoxin in patient blood. Over the years, few studies have reliably identified individuals who suffer the frequent passage of bacteria or their products into circulation because measurement of endotoxin in biological fluids is notoriously difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports identified associations of aortic stiffness with dysregulation in various metabolic pathways in the setting of type 2 diabetes. Treatment with an incretin mimetic was observed to improve carotidfemoral PWV in individuals with newly diagnosed type 2 diabetes [37] and serum levels of the acute phase reactant lipopolysaccharide-binding protein were shown to be associated with aortic PWV in patients with type 2 diabetes, especially in men [38]. Administration of sodium glucose co-transporter 2 inhibitor reduced aortic stiffness in type 2 diabetic female mice (db/db) [39].…”
Section: Prospective Association: Insulin Resistance Index Since Midmentioning
confidence: 99%